2022
DOI: 10.4103/aian.aian_392_21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Frequency, Clinical Spectrum and Outcomes of Pediatric Guillain-Barré Syndrome in India

Abstract: Objective: To study impact of COVID-19 pandemic on frequency, clinical/electrophysiological profile and treatment outcomes in pediatric Guillain-Barré syndrome (GBS). Background: GBS is the most frequent cause of pediatric acute flaccid paralysis. The effect of the COVID-19 pandemic on pediatric GBS is unclear in the literature. Methods: We conducted an ambispective, multicentric, cohort study involving 12 of 27 centres in GBS Consortium, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…[ 8 ] Similar findings were reported by an epidemiological study conducted in the United Kingdom. [ 3 ] These studies[ 3 5 ] also reported no significant differences between GBS patients triggered by COVID-19 and those without the infection. Demyelinating GBS is the most common subtype worldwide and was unsurprisingly the most common in this study as well.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…[ 8 ] Similar findings were reported by an epidemiological study conducted in the United Kingdom. [ 3 ] These studies[ 3 5 ] also reported no significant differences between GBS patients triggered by COVID-19 and those without the infection. Demyelinating GBS is the most common subtype worldwide and was unsurprisingly the most common in this study as well.…”
mentioning
confidence: 98%
“…[ 3 4 ] Experts have argued that an increase in GBS incidence might be masked by a decrease in GBS incidence due to other infectious triggers because of better hygiene, lockdown, and social distancing. [ 5 ] Studies from Japan and Brazil have reported a decreased incidence of infectious diseases during the lockdown because of these containment measures,[ 6 7 ] thereby indirectly reducing the occurrence of GBS. The “GBS consortium,” established in India with 26 centers,[ 5 ] found a reduction in the number of GBS cases during the COVID-19 pandemic compared with the same duration in the previous year in both adult[ 5 ] and pediatric groups.…”
mentioning
confidence: 99%
See 2 more Smart Citations